2006
DOI: 10.1021/jp0637274
|View full text |Cite
|
Sign up to set email alerts
|

In Situ FT-IR Studies on the Mechanism of Selective Catalytic Reduction of NOx by Propene over SnO2/Al2O3 Catalyst

Abstract: The mechanism of the selective catalytic reduction (SCR) of NOx by propene over SnO2/Al2O3 catalyst in the presence of oxygen has been investigated using in situ Fourier transform infrared (FT-IR) spectroscopy. In situ IR measurements indicate that acetate and formate, which are the derivatives of the partial oxidation of propene, play a crucial role in the formation of NCO by reacting with the reactive monodentate nitrate species. The resulting NCO species subsequently reacts with NOx to form N2. The presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Over the two catalysts, both the formate (1376, 1392 and 1590 cm -1 ) and acetate (1462 cm -1 ) bands decreased on exposure to NO + O 2 for 30 min, while the band intensities due to monodentate nitrate (1249 cm -1 and 1550 cm -1 ) and bidentate nitrate (1303 cm -1 ) increased. It should be noted that over the CeO 2 -SnO 2 /Al 2 O 3 catalyst, the acetate band almost disappeared after exposing to NO + O 2 for 30 min, indicating that the presence of CeO 2 promotes the reaction rate between the acetate and nitrate species, which is an important step in the HC-SCR over SnO 2 /Al 2 O 3 catalyst [16]. It also indicates that over the CeO 2 -SnO 2 /Al 2 O 3 catalyst, acetate is more reactive than formate.…”
Section: Influence Of Ceo 2 On the Consumption Of Adsorbed Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the two catalysts, both the formate (1376, 1392 and 1590 cm -1 ) and acetate (1462 cm -1 ) bands decreased on exposure to NO + O 2 for 30 min, while the band intensities due to monodentate nitrate (1249 cm -1 and 1550 cm -1 ) and bidentate nitrate (1303 cm -1 ) increased. It should be noted that over the CeO 2 -SnO 2 /Al 2 O 3 catalyst, the acetate band almost disappeared after exposing to NO + O 2 for 30 min, indicating that the presence of CeO 2 promotes the reaction rate between the acetate and nitrate species, which is an important step in the HC-SCR over SnO 2 /Al 2 O 3 catalyst [16]. It also indicates that over the CeO 2 -SnO 2 /Al 2 O 3 catalyst, acetate is more reactive than formate.…”
Section: Influence Of Ceo 2 On the Consumption Of Adsorbed Speciesmentioning
confidence: 99%
“…Based on the FT-IR studies, we have proposed a simplified reaction scheme for the NO x reduction with propene over SnO 2 /Al 2 O 3 catalyst [16]. Therein, the reaction starts with the formation of both adsorbed nitrates via NO oxidation by O 2, and formate and acetate species via the partial oxidation of propene.…”
Section: Influence Of Ceo 2 On the Consumption Of Adsorbed Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many problems were encountered in the application of NH 3 -SCR technology [3,4], such as catalyst deterioration caused by the ammonium sulphate deposition, ammonia slip, air heaters fouling, and high running cost [5][6][7]. In the past decades, various hydrocarbons [8][9][10][11][12][13][14] have been studied as reductant for the purpose of removing NO x in excess oxygen, which was expressed as HC-SCR, whereas their poor activity and selectivity under low temperature towards the aimed reaction make this technology hardly developed. Recently, hydrogen [15][16][17][18][19][20][21][22] has been proved to be effective reductant for NO x reduction in excess oxygen because of its high activity towards NO reduction and zero emissions of greenhouse gases in the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Hamada et al [9][10][11] have investigated the SCR of NO by C 3 H 8 (C 3 H 8 -SCR) over H-MFI and Al 2 O 3 , and proposed that NO 2 plays an important role for the apparent reaction in the following route: The C 3 H 8 -SCR was started by NO oxidization to NO 2 , and NO 2 produced by the reac-tion then reacted with C 3 H 8 to yield N 2 over the catalysts. Woo and co-workers [12] have investigated the SCR of NO by C 3 H 6 over SnO 2 /Al 2 O 3 using in situ Fourier transform infrared spectroscopy (FTIR), and suggested that the reaction begins with formation of adsorbed nitrate species, which are produced by NO oxidation. Mechanism of H 2 -assisted C 3 H 8 -SCR over Ag-MFI has also been investigated by Shimizu et al using FTIR spectroscopy [13].…”
Section: Introductionmentioning
confidence: 99%